Improving dryland seedling recruitment using fungicide seed coatings. Issue 1 (22nd February 2022) - Hoose, Benjamin W.; Geary, Bradley D.; Richardson, William C.; Petersen, Steven L.; Madsen, Matthew D.
Abstract: The success of seed‐based restoration in dryland regions of the world is often low or sporadic, with most mortality occurring between germination and emergence. Fungal pathogenesis is one process that may reduce seedling emergence and limit restoration success. Our objective was to determine whether fungicide seed coatings constitute an economically viable strategy for increasing emergence by reducing fungal pathogenesis and mortality. We performed an experiment across two sites and three years, using bluebunch wheatgrass ( Pseudoroegneria spicata ) as a model species. We found that fungicide coatings increased germination by 8.8% and emergence by 54.0% on average compared to the control. A cost analysis indicated that the fungicide coating was economically viable with an average estimated effective cost reduction of 18.8% under the study conditions. There was a strong interaction ( P < 0.001) between the effects of the fungicide coating, site and year on emergence. The fungicide coating increased emergence compared to the control in five of the six sites and years, with the effect ranging from a 33.7% decrease ( P = 0.042) to a 150.9% increase ( P = 0.004). The observed interaction was likely related to the effect of the hydrothermal microsite environment on disease severity. In the site and year that the fungicide coating performed worse than the control, prolonged periods of exceptionally low soil moisture may have reduced disease severity through a variety of individual and community scale mechanisms. Overall, these results indicate that fungicide seed coatings have the potential to improve dryland restoration efforts. Abstract : We demonstrated through field experiments that fungicide seed coatings have the potential to cost‐effectively increase seedling emergence in dryland restoration seedings. Thus, fungicide seed coatings constitute a promising tool for future restoration applications.